Karakteristik Pasien COVID-19 di Rumah Sakit Umum Daerah Dr. H. Chasan Boesoirie - Nur Upik En Masrika; Marhaeni Hasan; Yusril Yusran; Sonia Buyung (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Coronavirus disease-19 (Covid-19) is an infectious disease that is currently a topic of conversation and attention worldwide. The purpose of this study was to determine the characteristics of patients both clinically, laboratory results, co-morbidities, and outcomes of Covid-19 patients who were hospitalized in the Covid-19 Isolation Room (RIC) at Dr. H. Chasan Boesoirie Ternate Hospital. This research method is descriptive by using medical record data of 112 patients. The results of this study were mostly adults (26-45 years) 42.9%, female gender 54.5%, high school education background 49.1% and not having a job 36.6%, clinical symptoms of cough (64.3 %), co-morbidities of diabetes mellitus (22.3 %), and an increase in the parameters of leukocyte examination, NLR, INR, and D-Dimer. From 112 patients, 107 patients were declared cured with a negative result of the Covid-19 PCR-RT swab test (95.5%) and 5 people died (4.5%). The conclusion is that the characteristics of Covid-19 patients at the Dr. H. Chasan Boesoirie Ternate Hospital is an adult, female, high school education, does not have a job, has cough symptoms, comorbidities with diabetes mellitus, increased leukocytes, NLR, INR, and D-Dimer, and the patient went home because they was declared cured.